Outdoors USA / The Year Book of Agriculture - Time-Life Books (Washington : The United States Department of Agriculture, 1967)
Profusely illustrated text and illustrated diagrams describe how to design outdoor spaces for patios, porches, terraces and yards.
Designs for outdoor living -- Outdoor furnishings -- Dramatic effects with low-voltage lighting -- Outdoor floors -- Fountains and pools -- Enlivening enclosures -- Tools for outdoor projects.
Includes index.
Keywords: Garden structures; Outdoor furniture; Exterior lighting